Britain's Health Services (London : Communist Party of Great Britain)
1942-10 1942 1940s 40 pages Non-Resident: 2 Senior physicians 3 Senior surgeons 1 Obstetrician and gynaecologist 1 Ophthalmologist 1 E.N.T. surgeon 1 Orthopaedic surgeon 1 Pediatrician 3 Dental surgeons 3-4 Anaesthetists These would be " honoraries," i.e. not paid for services by hospital or general patients. There are, of course, adequate returns in other ways for work done by this staff. 1 Pathologist 1 Radiologist (X-ray) These would receive "fees" but have semi-honorary status. Resident: 1 Resident surgical officer 2-3 Junior house officers Full-time. Nursing: Matron, Sisters, Staff Nurses and Probationers 116 Administrative: Superintendent, Accountant and assistants 13 Medical and Nursing Auxiliaries: Dispensers (3), Laboratory Assistants (4), Masseuses (3), Radiographers (2), Almoners (2) 14 Domestic Laundry: Kitchen (9), Cleaners (6), Housemaids (10), Wardmaids (14), Seamstresses (2), Male Porters (11) 52 Maintenance: Carpenter (1), Painter (1), Engineer (1), Stokers (3), Gardener (1 or 2), Handymen (2).................... 10 Total (excluding Honorary medical staff) 209 Staffing of an L.C.C. Hospital (Fulham Hospital, 559 beds). Local Authority hospitals have no "honoraries"; visiting consultant staff are paid. Medical: Resident 8 Nursing: Male 6 Female 188 Administrative (Note. — Much administrative work done at County Hall) 7 Medical and Nursing Auxiliaries: Dispensers (2), Radiographers (2), Masseuses (3), Clergy (3), Others (3) ................ 13 Domestics: Male (28), Female (103) 131 Maintenance: Staff employed centrally and sent from hospital to hospital - Total 353 5. WORKERS IN HEALTH SERVICES The above paragraphs on typical staffing have been inserted to illustrate the diversity of professions and trades involved in hospital work. There is a total of approximately 500,000 health workers and whilst no 32 15X/2/103/252